2007
DOI: 10.1105/tpc.107.055061
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosylation of Peroxiredoxin II E Promotes Peroxynitrite-Mediated Tyrosine Nitration

Abstract: Nitric oxide (NO) is a free radical product of cell metabolism that plays diverse and important roles in the regulation of cellular function. S-Nitrosylation is emerging as a specific and fundamental posttranslational protein modification for the transduction of NO bioactivity, but very little is known about its physiological functions in plants. We investigated the molecular mechanism for S-nitrosylation of peroxiredoxin II E (PrxII E) from Arabidopsis thaliana and found that this posttranslational modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
231
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(242 citation statements)
references
References 52 publications
5
231
1
5
Order By: Relevance
“…For example, in a number of experimental models, NO or nitrosative stress induces the expression of specific Prxs, including Prx1 (39,40). Other recent studies have indicated that S(NO) can directly modulate several members of the Prx family by means of S-nitrosylation (19,20,23). In this study we provided additional mechanistic insights into the regulation of a 2-Cys Prx by SNO.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…For example, in a number of experimental models, NO or nitrosative stress induces the expression of specific Prxs, including Prx1 (39,40). Other recent studies have indicated that S(NO) can directly modulate several members of the Prx family by means of S-nitrosylation (19,20,23). In this study we provided additional mechanistic insights into the regulation of a 2-Cys Prx by SNO.…”
Section: Discussionmentioning
confidence: 64%
“…In neuronal cells, nitrosylation of Prx2 has been shown to inhibit its activity and thereby to contribute to oxidative stress and cellular damage (19). Nitrosylation likewise inhibits the activity of plant Prx II E (20). Prx1 was found to be nitrosylated in endotoxin-stimulated macrophages (21,22), and recent studies indicate that nitrosylation protects Prx1 from over-oxidation (23).…”
mentioning
confidence: 99%
“…In particular, S-nitrosylation of peroxiredoxin II E has been demonstrated to inhibit its activity involved in hydroperoxide reduction and peroxynitrite detoxification [37], and S-nitrosylation of NPR1 is critical for the regulation of redox-based conformational changes that directly determine the NPR1 activity [35]. In addition, the Arabidopsis METACASPASE9 activity is regulated by S-nitrosylation, providing a possible link between the redox-based posttranslational modification mechanism and biochemical execution of cell death in plant cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, S-nitrosylation, the covalent addition of an NO molecule to a cysteine thiol of a protein or a peptide, is a key destination of the gaseous hormone and a redox-based posttranslational modification mechanism. S-nitrosylation appears to be an important mechanism to regulate the activity and stability of many proteins and enzymes [24,[34][35][36][37][38]. In this complicated, yet not well-understood process, S-nitrosoglutathione (GSNO), derived by S-nitrosylation of the antioxidant tripeptide glutathione, is a major reservoir of biologically active NO.…”
Section: Introductionmentioning
confidence: 99%
“…À ce jour, une cinquantaine de protéines S-nitrosylées a ainsi été identifiée, dont une dizaine ont fait l'objet d'études fonctionnelles approfondies (Tableau I). Il ressort de ces études que la S-nitrosylation module l'activité de ces protéines en ciblant directement des résidus Cys de sites actifs [24][25][26][27][28], en promouvant la formation de ponts disulfures [29,30], et en bloquant la fixation de cofacteurs (FAD ou ATP) par encombrement stérique [31,32]. Les données acquises pour les protéines NPR1 (nonexpressor of pathogenesis-related gene 1) et RBOHD (respiratory burst oxidase homologue D) sont détaillées ci-dessous à titre d'exemple (Figure 2).…”
Section: Identification Et Premières Analyses Fonctionnelles Des Protunclassified